PERANAN DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA DALAM PENGENDALIAN PERTUMBUHAN PENDUDUK KOTA SEMARANG - Yulita Nilam Fridiyanti; Agus Riyanto; Suharto; Zudi Setiawan (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This research was conducted at the Semarang City Population and Family Planning Office. The target of the Population Control and Family Planning Service is the realization of stable population growth and the creation of quality families in the city of Semarang in order to avoid overcrowding with limited employment and pay attention to the health of fertile couples (PUS) and the growth and development of children born. This study aims to measure the extent of the population control agency's role in controlling the rate of population growth and the obstacles encountered in controlling the population of Semarang City using a qualitative descriptive research method. The results of the research show that the Office of Population Control, Family Planning, Women's Empowerment and Child Protection have played an optimal role. However, there are several obstacles that must be overcome, such as a lack of quality personnel, supporting facilities for service mobilization and program budgets that have been trimmed for other programs. In this regard, the efforts made to deal with obstacles include organizing family planning coaching with a priority scale, Refreshing Family Planning Cadres Activities with health protocol guidelines and coordinating synergistically regarding the need for operational infrastructure for family planning services